Digital circuit analysis and design with Simulink modeling and introduction to CPLDs and FPGAs - Karris, Steven T. ([Fremont, Calif.?] : Orchard Publications, 2007)
This book is an undergraduate level textbook presenting a thorough discussion of state-of-the-art digital devices and circuits. It is self-contained.
Common number systems and conversions -- Operations in binary, octal, and hexadecimal systems -- Sign magnitude and floating point arithmetic -- Binary codes -- Fundamentals of Boolean algebra -- Minterms and maxterms -- Combinatorial logic circuits -- Sequential logic circuits -- Memory devices -- Advanced arithmetic and logic operations -- Introduction to field programmable devices -- Introduction to MATLAB -- Introduction to Simulink -- Introduction to ABEL hardware description language -- Introduction to VHDL -- Introduction to Verilog -- Introduction to boundary scan architecture.
Includes bibliographical references and index.
Print version record.
Keywords: Field programmable gate arrays; Programmable logic devices; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- VLSI & ULSI; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- Logic; COMPUTERS -- Logic Design; Field programmable gate arrays; Programmable logic devices; Electronic books; Electronic books